1986
DOI: 10.3109/00365518609083728
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urinary C-peptide in the classification of adult diabetics

Abstract: Plasma and urinary C-peptide determinations in the discrimination between insulin-requiring and non-insulin-requiring diabetes were elevated in 61 adult diabetics. Specimens for C-peptide determinations were taken on two consecutive days: on the first day plasma C-peptide concentrations were determined before and 6 min after intravenous glucagon administration. On the second day 2- and 4-h urinary C-peptide excretion was measured after an individual breakfast. Results of urinary C-peptide analyses were express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Thus, the predictive value of a stimulated C-peptide level above and below 0.60 nmol/1 as indicator of Type 2 and Type 1 diabetes was 91% and 78%, respectively. A plasma C-peptide level of 0.60 nmol/1 has previously been suggested to discriminate between Type 2 diabetic subjects with and without insulin requirement [8,9]. In our study, approximately 75% of patients with a stimulated plasma C-peptide concentration from 0.32 nmol/1 to 0.60 nmol/1 were clinically Type 2 diabetic subjects.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Thus, the predictive value of a stimulated C-peptide level above and below 0.60 nmol/1 as indicator of Type 2 and Type 1 diabetes was 91% and 78%, respectively. A plasma C-peptide level of 0.60 nmol/1 has previously been suggested to discriminate between Type 2 diabetic subjects with and without insulin requirement [8,9]. In our study, approximately 75% of patients with a stimulated plasma C-peptide concentration from 0.32 nmol/1 to 0.60 nmol/1 were clinically Type 2 diabetic subjects.…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, Koskinen et al reported that urinary C-peptide was less H. J. Gjessing et al: C-peptide and clinical type of diabetes sensitive than post glucagon C-peptide in the discrimination between Type 2 diabetic subjects with and without insulin requirement [9]. The most important reason probably is a large variability of urinary C-peptide excretion [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine samples collected over a period of four hours and single post stimulated UCP have been shown to be significantly correlated with serum insulin and serum C-peptide in non-diabetic subjects 26 , and in insulin treated diabetic patients 7 . Correcting for creatinine adjusts urine C-peptide concentration for variation in urine concentration and enables the use of 'spot' urine samples in place of 24-h urine collection.…”
Section: Urine C-peptidementioning
confidence: 98%
“…There is extensive evidence that C-peptide can be used to differentiate between the classification of Type 1 diabetes and Type 2 diabetes [6][7][8][9][10] . C-peptide is a good candidate biomarker to differentiate patients with Maturity Onset Diabetes of the Young (MODY) from Type 1 diabetes.…”
Section: C-peptide and Differentiating Subtypes Of Diabetesmentioning
confidence: 99%